2005
DOI: 10.1038/nchembio718
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput assays for promiscuous inhibitors

Abstract: High-throughput screening (HTS) searches large libraries of chemical compounds for those that can modulate the activity of a particular biological target; it is the dominant technique used in early-stage drug discovery. A key problem in HTS is the prevalence of nonspecific or 'promiscuous' inhibitors. These molecules have peculiar properties, act on unrelated targets and can dominate the results from screening campaigns. Several explanations have been proposed to account for promiscuous inhibitors, including c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
378
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 324 publications
(401 citation statements)
references
References 14 publications
7
378
2
1
Order By: Relevance
“…The inhibition proved to be specific as the compounds did not affect neither CaM nor the pyrophosphatase used in the assay (see SI Text). The presence of detergent in the assay also prevented promiscuous inhibitory effects (46). These results showed that modeling transition paths is a useful tool for drug design to enlarge the search for inhibitors to new chemical families.…”
Section: Discussionmentioning
confidence: 71%
“…The inhibition proved to be specific as the compounds did not affect neither CaM nor the pyrophosphatase used in the assay (see SI Text). The presence of detergent in the assay also prevented promiscuous inhibitory effects (46). These results showed that modeling transition paths is a useful tool for drug design to enlarge the search for inhibitors to new chemical families.…”
Section: Discussionmentioning
confidence: 71%
“…These include the sensitivity of inhibition to the presence of a large amount of secondary protein, such as bovine serum albumin (BSA) 12,13 , time-dependence of inhibition and sensitivity to the concentration of the target protein 8,9 . Inhibition of Sup35 polymerization displayed all of these traits.…”
Section: Online)mentioning
confidence: 99%
“…The assay was miniaturized to a final volume of 3 ÎŒL in 1536-well format by direct volume reduction. Additionally, in order to prevent peptide and protein absorption to the polystyrene wells due to the increased surface-to-volume ratio and to minimize the interfering effect of promiscuous inhibitors acting via colloidal aggregate formation [4,5], we included detergent (0.01 % Tween-20) in the assay buffer.…”
Section: Assay Principle Miniaturization and Optimizationmentioning
confidence: 99%
“…In addition to the expansiveness and low definition of the interacting protein surfaces, technical issues pertaining to assay design and screening artifacts further complicate the identification of true PPI disrupters [3]. For example, colloidal aggregates spontaneously formed by certain compounds might reach the size and topology sufficient to perturb protein-protein interactions in a reproducible yet non-specific and biologically irrelevant manner [2,4,5].…”
Section: Introductionmentioning
confidence: 99%